Inhibition of Klebsiella pneumoniae Growth and Capsular Polysaccharide Biosynthesis by Fructus mume. (26th August 2013) - Lin, Tien-Huang; Huang, Su-Hua; Wu, Chien-Chen; Liu, Hsin-Ho; Jinn, Tzyy-Rong; Chen, Yeh; Lin, Ching-Ting
Abstract : Klebsiella pneumoniae is the predominant pathogen isolated from liver abscess of diabetic patients in Asian countries. With the spread of multiple-drug-resistant K. pneumoniae, there is an increasing need for the development of alternative bactericides and approaches to block the production of bacterial virulence factors. Capsular polysaccharide (CPS), especially from the K1 and K2 serotypes, is considered the major determinant for K. pneumoniae virulence. We found that extracts of the traditional Chinese medicine Fructus mume inhibited the growth of K. pneumoniae strains of both serotypes. Furthermore, Fructus mume decreased the mucoviscosity, and the CPS produced in a dose-dependent manner, thus reducing bacterial resistance to serum killing. Quantitative reverse transcription polymerase chain reaction analyses showed that Fructus mume downregulated the mRNA levels of cps biosynthesis genes in both serotypes, possibly by increasing the intracellular iron concentration in K. pneumoniae . Moreover, citric acid, a major organic acid in Fructus mume extracts, was found to have an inhibitory effect on growth and CPS biosynthesis in K. pneumoniae . Taken together, our results indicate that Fructus mume not only possesses antibacterial activity against highly virulent K. pneumoniae strains but also inhibits bacterial CPS biosynthesis, thereby facilitating pathogen clearance by the host immune system.